An Update on the Management of Endodontic Biofilms Using Root Canal Irrigants and Medicaments - Mohammadi, Zahed; Soltani, Mohammad Karim; Shalavi, Sousan (Iranian Endodontic Journal, 2014)
Microbial biofilm is defined as a sessile multicellular microbial community characterized by cells that are firmly attached to a surface and enmeshed in a self-produced matrix of extracellular polymeric substances. Biofilms play a very important role in pulp and periradicular pathosis. The aim of this article was to review the role of endodontic biofilms and the effects of root canal irrigants, medicaments as well as lasers on biofilms. A Medline search was performed on the English articles published from 1982 to 2013 and was limited to papers published in English. The searched keywords were “Biofilms AND endodontics”, “Biofilms AND sodium hypochlorite”, "Biofilms AND chlorhexidine", "Biofilms AND MTAD", "Biofilms AND calcium hydroxide", “Biofilms AND ozone”, “Biofilms AND lasers” and "Biofilms AND nanoparticles". The reference list of each article was manually searched to find other suitable sources of information.